Customer Satisfaction as a Mediator for the Influencer and Word of Mouth on Online Purchase Decisions for Fashion Products in Denpasar City - FERAYANTI, Kadek Dewi; WAHYUNI, Ni Made; LAKSMI, Putu Ayu Sita (PT Keberlanjutan Strategis Indonesia, 2024)
The aim of this research is to determine the influence of customer satisfaction in mediating influencers and electronic word of mouth on online purchasing decisions for fashion products in Denpasar City. Data collection was carried out through surveys using questionnaires. The population in this study was adjusted to the analysis model used, namely Partial Least Square, with sample determination using the Hair formula. The sample in this study was 90 respondents from the people of Denpasar City who made online purchases of fashion products. The data analysis technique used is SEM PLS analysis. The research results show that influencers have a positive and significant effect on customer satisfaction. Influencers have a positive but not significant effect on purchasing decisions. Word of mouth has a positive but not significant effect on customer satisfaction. Word of mouth has a positive and significant effect on purchasing decisions. Customer satisfaction has a positive and significant effect on purchasing decisions. Customer satisfaction mediates the influence of influencers on purchasing decisions. Customer satisfaction mediates the influence of word of mouth on purchasing decisions.